Stroke Rates: 1980–2000: The Minnesota Stroke Survey - Lakshminarayan, Kamakshi (Oxford University Press, 2009)
In this paper, the authors report trends in hospitalized stroke rates among Minneapolis-St. Paul, Minnesota (population 2.6 million) metropolitan area residents aged 30–74 years from 1980 to 2000. Cases were identified from lists of discharge diagnoses provided by hospitals serving the target population. Age-adjusted, sex-specific stroke attack rates were computed for each survey year by using 5 different diagnostic definitions: 2 based purely on International Classification of Diseases, Ninth Revision (ICD-9) codes and 3 including clinical and neuroimaging criteria. Stroke rates, as measured by a highly specific clinical definition, remained stable from 1980 to 2000 for women. For men, these rates declined modestly from 1980 to 1990 and leveled off during 1990–2000. In contrast, use of stroke-related ICD-9 discharge codes declined significantly from 1980 to 2000: 35% among men and 16% among women. Neuroimaging use increased significantly from 75% of cases in 1980 to 98% in 2000. Short-term (28-day) stroke survival improved significantly, by 16% for women and 12% for men, from 1980 to 2000. The decline in stroke ICD-9 code usage reflects the influence of increased neuroimaging on discharge coding. The improved short-term survival in the face of stable, clinically defined stroke rates may imply treatment advances or ascertainment of less severe strokes, possibly masking a true decline in stroke rates.